Potential Clinical Applications of Exosomal Circular RNAs: More than Diagnosis - Molibeli, Kearabetsoe Matseliso; Hu, Rong; Liu, Yuze; Xiong, Dehui; Tang, Lijun (Frontiers in Molecular Biosciences, 2021)
Exosomes are small vesicles derived from cells used as cell-to-cell communication goods in numerous diseases including tumorigenesis, neurological diseases, cardiovascular diseases and other diseases. Circular RNAs (circRNAs) are an innovative constituent of non-coding endogenous RNAs generated through backsplicing, catalyzed by RNA polymerase Ⅱ. These non-coding RNAs have been suggested to control gene expression through miRNA sponging, RNA-binding protein regulation and translational capabilities. Genome-wide RNA sequence analyses observed that circRNAs were stably improved in exosomes in association to parental cells. Little attention has been dedicated to exosomal circRNAs (exo-circRNAs). However, research has demonstrated that exo-circRNAs may have important regulatory functions because of their stability in cells and within exosomes. If well understood, the precise roles and mechanisms of exo-circRNAs might surge the impending clinical applications of these molecules as markers in the identification, prediction and treatment of various diseases. In this review, we outline recent findings regarding exo-circRNAs which includes their functions and highlights their potential applications and therapeutic targets in human diseases.